Help me to come out gracefully! Working with lesbian, gay, and bisexual, people affected by cancer to develop a national practitioner guide supporting inclusive care. (May 2023) - Hill, G.; Bulley, C.
Abstract: Introduction: The healthcare support needs of the lesbian, gay, bisexual (LGB) and transgender community are becoming an emerging area of healthcare research. Providing person-centred care is World Health Organisation policy and as such it is important that Radiography services can demonstrate areas in which they are working with people to design, develop and feedback on the services that they receive. This research aimed to establish how cancer treatment impacted on the identities of LGB people, their experiences of care, and their engagement with developing a practitioner guide. Methods: This cooperative inquiry is underpinned by person-centred philosophy and participatory research principles. Participants were nine lesbian, gay, and bisexual people affected by cancer. Each engaged in two facilitated, audio-recorded conversations to explore their experiences of cancer care. An analytical framework based on Mezirow's Transformational Theory was used to organise the data, followed by detailed content analysis to develop themes. Results: Participants included men and women, aged 45–68, who had experienced different cancers. They explored how cancer treatment had impacted on them, and worked with the researcher and stakeholders to establish a seven-recommendation practitioner guide aimed at improving LGB people's care experiences. Their accounts revealed a broad range of issues that both corroborate and build on existing evidence. Themes highlighted expectations and experiences of both assumptions and prejudice in healthcare interactions. These experiences, along with misinterpretation of relationships with significant others, led to feelings of discomfort and reserve about self-expression. Findings of the research are presented in the following key areas: Dilemmas of attending oncology appointments; Inclusive experiences of care; and Formulation of the practitioner guide. Conclusion: The research findings enabled development of a national practitioner guide with the participants and key stakeholders to raise awareness of the needs of LGB persons affected by cancer and support better care. Implications for practice: By providing real-life accounts this research adds to understanding of how LGB persons interact with services, developing evidence to support cultural competence within the profession of Radiography and oncology services more broadly.